Being Awareness Ecology Citizenship Through Waste Bank Management (Study In Community Enzyme Indonesian Service) - Prini Desima Evawani Ambarita; Cecep Darmawan; Rahmat Rahmat; Syaifullah Syaifullah (Jurnal Ilmu Sosial Mamangan, 2024)
This study about form awareness ecology citizenship through waste bank management in the Community Enzyme Indonesian Service. The goal study is For understand how is the waste bank in the Community Enzyme Bakti Indonesia contributes to awareness ecology citizens as well How its management influence perception and behavior they to environment. Method used is qualitative studies case. Data collection was carried out with  interview in-depth, observation participatory, and documentation. Data is collected from waste bank members and stakeholders interest related. Analysis qualitative show that the waste bank in the Community Enzyme Bakti Indonesia does not only role as means management trash, but also as receptacle For build awareness ecology citizenship. Through participation in activity management rubbish in the Community Enzyme Bakti Indonesia, member of the waste bank develop more understanding in about importance guard environment. They also experience it change behavior, such as practice cycle repetition and subtraction rubbish plastic. Waste bank management also has an influence perception public to environment, strengthening the sense of belonging towards their territory, and improve collaboration between citizens. Findings This underline importance approach participatory in build awareness ecology citizenship through waste bank management, which can become an inspirational model For initiative similar in various community